Forming an image of complex parts of the structure of the refracting boundary - Verpahovskaya, A. O. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2012)
Migration transformations of the field of refracted waves make possible imaging of structural features of irregularly shaped refraction boundary in deep dynamic section. First arrivals of refracted waves are persistently traced on the wave field along considerable distances from the source of wave excitation that is a guarantee of a high definition of recreation of structural details of the studied boundary while processing the data of regional seismic exploration. Special features of accomplishment of finite-difference migration of the refracted wave field under conditions of refracting boundary structure complicated by faults have been considered as well as methodic problems, related to valuation of the wave field interval where refracted waves are registered depending on the velocity model of the medium. The results of the studies are demonstrated on the model and practical materials.